ANALISIS FAKTOR PENYEBAB KETERLAMBATAN MEMBACA PADA SISWA BERKESULITAN BELAJAR KELAS IV SDN BIBISLUHUR 1 SURAKARTA DITINJAU DARI FAKTOR EKSTERNAL (LINGKUNGAN) TAHUN AJARAN 2025/2026 - Kusuma Asri, Novia; Heru Sri Suryanti, Hera; Jumanto, Jumanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the presence of students with learning difficulties who experienced reading delays in Grade IV B of SD Negeri Bibisluhur 01 Surakarta. The reading delays were indicated by difficulties in recognizing letters, combining letters into words, reading fluently, and comprehending reading texts. This study aimed to analyze the factors causing reading delays in students with learning difficulties from the perspective of external (environmental) factors.This research employed a qualitative method with a case study approach. The research subjects consisted of three students with learning difficulties who experienced reading delays, their classroom teacher, and their parents. Data were collected through observation, interviews, and documentation. Data validity was ensured through source triangulation and technique triangulation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings revealed that the students’ reading delays were reflected in difficulties related to letter recognition, word decoding, reading fluency, and reading comprehension. The external factors influencing reading delays included family environment, school environment, technology use, and low reading motivation and interest. Family-related factors involved limited reading habits at home and insufficient parental assistance. School-related factors included limited opportunities for individual reading support and suboptimal utilization of literacy facilities. Excessive use of digital devices compared to reading activities, along with low reading motivation, also contributed to the slow development of students’ reading skills. Therefore, collaboration among schools, teachers, and parents is necessary to improve students’ reading abilities effectively.